Профессиональное самосознание будущих психологов в условиях выбора специализации - Попова, Галина Викторовна (НТУ "ХПИ", 2014)
В статье обсуждаются виды специализаций профессии "психолог" в современном обществе, их восприятие будущими психологами с точки зрения сферы и технологий деятельности. Приводятся данные исследования содержания профессионального самосознания и характеристик эмоциональных аспектов профессионального самоопределения студентов-психологов, находящихся в ситуации выбора дальнейшего конкретного профессионального пути. Обсуждаются условия формирования адекватной профессиональной идентичности студентов-психологов в вузе.

In contemporary Ukraine professional activities of psychologists expand and become directly related not only to the interests of individuals, but also organizations and the general public, there are new specialization of the profession. The peculiarity of becoming a professional psychologist is that getting psychological education does not guarantee the quality of its direct occupation. Professionalization of the expert in the field of psychology is closely related to the adequacy of the development of personality structures, as a professional identity, professional identity, professional self-concept. To be held as a specialist in the field of psychological practice is not only important to have knowledge, but also to be prepared personally to their use.
Professional indentity of future psychologists in conditions of choice of specialization
Keywords: специализация профессии психолог; общество; профессиональный путь; студенты-психологи; professional identity